Survey of rice (Oryza sativa L.) production ecosystems in northern Ghana confirms low risk of exposure to potential toxic elements from local grain consumption - Eureka E.A. Adomako; Kow Aboagye-Ghunney; Prince Owusu (Canadian Science Publishing, 2024)
Expanding local rice production to meet consumer demand is a priority action under the Government of Ghana's Planting for Food and Jobs initiative. While studies on yield-enhancing interventions abound, fewer studies focus on food safety issues (e.g., the potential toxic element status of the production ecosystems). This study was, therefore, conducted to bridge the knowledge gap. Chemical analyses were conducted on water, soil, and rice grain samples from different production ecosystems in the Northern and Upper East regions of Ghana. Statistical analysis of the data showed that soil and rice grain arsenic concentrations were significantly higher (P < 0.001) in the Upper East region. In the Northern region, mean cadmium concentration in rice grains from the irrigated lowland fields (0.023±0.003 mg/kg) was significantly higher than in grains from the rainfed fields. All recorded concentrations of rice grain arsenic, cadmium, and lead were, however, within permissible limits, indicating a low risk of dietary exposure. The observed differences in concentrations within and between regions suggest that soil texture and other geogenic factors could influence the potential toxic element status of the rice production ecosystems. Regular monitoring is, therefore, recommended to maintain the safety of Ghana's locally produced rice for human consumption.